Thermal imaging and physiological responses of crossbred goats under different housing system during hot humid season - SV Singh, AK Misra1, Gaurav Kumar and Apeksha Ukey (Indian Journal of Dairy Science, 2023)
In order to observe the effect of hot humid (July-August) season on physiological responses and skin surface temperature, eighteen adult female crossbred goats were selected divided equally into three groups i.e. Group I (control), Group II (modified shed) and Group III (open environment) based on their body weight. These animals were fed as per the standard feeding schedule followed at NDRI, Karnal. The average respiration rate of group I, II and III was 76.11±1.03, 67.22±0.06 and 70.49±0.61 per minute respectively during morning hours. The RR increased significantly during afternoon over morning values in all the groups due to increase of THI. The rectal temperature of goats during morning hours was 38.73±0.02, 38.57±0.03 and 38.68±0.03°C in group I, II and III respectively and no significant change in RT was observed during the afternoon. The overall lowest and highest skin temperature were recorded at the lower part of legs and ears respectively in group I and II, whereas in group III the highest skin temperatures was found to be at dorsal and lowest at ventral region of the body. The information generated may serve as normal reference values for crossbred goats under different housing conditions and may be useful for predicting the animal welfare and prognosis of diseases.